Effects of desensitizing dentifrices on dentin tubule occlusion and resistance to erosive challenges - Xiaoyi Zhao; Lin Wang; Jie Pan; Hans Malmstrom; Yan-Fang Ren (BMC, 2021)
Abstract Background Many studies have demonstrated efficacy of casein phosphopeptide (CPP) containing products for dentin tubule occlusion for treatment of dentin sensitivity, but their effectiveness under dynamic erosive challenges remains to be elucidated. The purpose of the present study was to investigate the effectiveness of a desensitizing dentifrice containing CPP in occluding dentin tubules and resisting erosive challenges in comparison to that containing polyvinyl methyl ether/maleic acid (PVM/MA) copolymers. Methods A total of 33 dentin discs were prepared from coronal sections of human third molars and divided into 3 groups: a toothpaste containing CPP; a toothpaste containing PVM/MA and submicron silica; and a regular toothpaste (Controls). A soft-bristle toothbrush was used to brush the dentin discs with the dentifrices for 45 strokes in 30 s at a force of approximately 200 g. The brushing cycle was repeated after immersion of the dentin discs in artificial saliva overnight. The dentin discs were then challenged in orange juice for 10 min in an incubator rocking at 120 rpm. Three fields were randomly selected on each dentin disk surface to assess dentin tubule occlusions after each brushing cycle and after orange juice challenge with a 3D laser scanning microscope. Specimen cross sections were examined with a scanning electron microscope equipped with energy dispersive spectroscopy (SEM/EDS). Results After the first and second cycles of brushing, dentin tubules were occluded on average by 56.3% and 85.7% in CPP group, 66.2% and 88.1% in PVM/MA group, and 0.0 and 13.0% in the controls, respectively. There were no statistically significant differences in dentin tubule occlusions between the CPP and PVM/MA groups after two cycles of brushing (p>0.05). After dynamic erosive challenges with orange juice, 20.3% of the dentin tubules in the CPP group, 79.1% in the PVM/MA group and none in the control remained occluded (P<0.05). SEM/EDS imaging showed that dentin tubules were blocked with plugs containing dentifrice substances in CPP and PVM/MA groups after treatments, but none in the controls. Conclusions Desensitizing dentifrices containing CPP or PVM/MA could effectively occlude dentin tubules after two cycles of brushing. PVM/MA in combination with submicron silicon dioxide exhibited stronger resistance to dynamic erosive challenges by acidic beverages. Inorganic fillers that can enter dentin tubules and resist erosive challenges may be key for desensitizing dentifrices.